Holly’s Personality Alteration as Portrayed in Ahern’s P.S. I Love You - Pramudana Ihsan (Universitas Muhammadiyah Surabaya, 2015)
This study attempts to discuss the issue raised from the novel entitled P.S. I Love You writtenby Cecilia Ahern. This novel provides a personality alteration performed by the main character, Holly Kennedy who is portrayed as dependent, selfish, and fragile person. The writer mainly uses qualitative method to present the data, furthermore the data obtained will be analyzed vividly with intrinsic elements: characterization and plot. To get a profound understanding, he divides characterization into character and characteristics while plot is sharpened into conflict. Thus problems arisen in Holly’s adult life will be taken out and discussed further using two elements of conflict: man vs man and man vs self. The result is a force for Holly Kennedy to have a significant personality alteration into a better one. In conclusion, this paper is aimed at finding the personality alteration performed by Holly Kennedy.